Comparison of rye, triticale, durum wheat and bread wheat genotypes for Fusarium head blight resistance and deoxynivalenol contamination. (15th November 2019) - Gaikpa, David Sewordor; Lieberherr, Bärbel; Maurer, Hans Peter; Longin, C. Friedrich H.; Miedaner, Thomas
Abstract: Small‐grain winter cereal crops can be infected with Fusarium head blight (FHB) leading to mycotoxin contamination and reduction in grain weight and quality. Although a number of studies have investigated the genetic variation of genotypes within each small‐grain cereal, a systematic comparison of the winter crops rye, triticale, durum and bread wheat for their FHB resistance, Fusarium ‐damaged kernels (FDK) and deoxynivalenol (DON) contamination across species is still missing. We have therefore evaluated twelve genotypes each of four crops widely varying in their FHB resistance under artificial infection with one DON‐producing F. culmorum isolate at constant spore concentrations and additionally at crop‐specific concentrations in two environments. Rye and triticale were the most resistant crops to FHB followed by bread and durum wheat at constant and crop‐specific spore concentrations. On average, rye accumulated the lowest amount of DON (10.08 mg/kg) in the grains, followed by triticale (15.18 mg/kg) and bread wheat (16.59 mg/kg), while durum wheat had the highest amount (30.68 mg/kg). Genotypic variances within crops were significant ( p  ≤ .001) in most instances. These results underline the differing importance of breeding for FHB resistance in the different crops.